The Benefits of Laughing Quigong on the Perceived Stress and Heart Rate - Wang, Ying-Chuan; Chiang, Sheng-Ta; Chiang, Hui-lin; Huang, Gui-Shuai; Gao, Rui-Xie; Chang, Yaw-Wen (Archives of Clinical and Biomedical Research, 2020)
The main objectives of this study were to explore the influence of Laughing Qigong on health promotion using spectral heart rate variability (HRV) analysis as well as whether any changes in autonomic nervous activity occurred after participating. This study employed a cross-sectional research design and recruited participants into a Laughing Qigong or normal control group. It used questionnaires to collect data and conducted an HRV analysis checkup before and after a Laughing Qigong intervention (30 min) was administered. Chi-square tests, Fisher’s exact test, and t tests were used to assess the relationships between the frequency of Laughing Qigong and health condition, pressure, and HRV statuses. Members of the Laughing Qigong group were older with a mean age of 42.15 years, whereas that of the controls was 34 years, which reached a significant difference (p=0.015); no significant differences were found in numerous other variables, including sex, diastolic blood pressure, body mass index, pregnancy status, and medical history. The Laughing Qigong group was further divided into two subgroups by exercise regularity (regular and irregular) and the data were reanalyzed, revealing some differences between the regular (n=18) and irregular (n=30) groups. In the regular group, a paired t test revealed significance in standard deviation of the NN interval (SDNN) change; however, it also revealed significantly decreased root-mean-square successive difference (RMSSD) in the irregular group. Therefore, we inferred that regularly practicing may regulate heart function. HRV analysis findings showed that the study group had higher sympathetic activity and lower parasympathetic activity, and this phenomenon was more obvious after the laughter program. Even though the influences of age, physical conditions, and external factors on HRV could not be overcome, autonomic nervous activity could reach a certain level of balance and the participants&rs